Family firm : a distinctive form of organization - Micelotta, Evelyn; Benedetti, Carlotta; Rovelli, Paola (Cambridge : Cambridge University Press, 2023)
This title reinvigorates calls to explore avenues to research on organization theory and family business in three areas: hybridity, paradoxes, and temporality.
Also issued in print: 2023.
Includes bibliographical references.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 2, 2023).
Keywords: Family-owned business enterprises -- Social aspects; Organizational sociology